Training Google Form as an Online Learning Evaluation Tool for Teachers at SDN Nusa Indah Subang Using the Method KulWApp - Efrina Aryani; Syifaul Fuada (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
A workshop on making Google Form-based learning evaluation questions for teachers at the Elementary School of Nusa Indah, Dangdeur Village, Subang District, West Java Province, was held successfully on December 5, 2020. This workshop aims to assist elementary school teachers in providing interesting online learning evaluations (not monotonous learning); this happens because so far, the assignment for evaluation purposes has only been carried out through the chat method (WhatsApp group), where the problem found is the teacher has difficulty recapitulating the student's assignments result. Later, the students get bored quickly because there is no variation in online evaluations, and parents have difficulty understanding the questions photographed by the teacher. Five teachers attended the training, carried out textually on the WhatsApp group. The implementation of this workshop runs smoothly, as expected. Therefore, the goals can be achieved in terms of teachers, students, and parents’ perspectives. The teacher can create simple questions on Google form. To implement this workshop, long-distance learning barriers in the Elementary School of Nusa Indah, especially related to assignments/online evaluation, can be overcome.